In search for an identity an urban design framework for imageable gateway nodes - Baria, Richelle Rhea R. (College of Architecture, University of the Philippines Diliman, 2009)
Designing for imageability has been an interest of many throughout history and all over the world. One of places that can immediately evoke a memorable image is the gateway node. A gateway is a visible and perceptible entry or exit point from one local to another. A gateway node is a place where this entry point also functions as a node, where there is a significant number of people or activities, such as a multi-modal interchange, a transit station, or a commercial core. Since movement and concentration of people and the experience of city life is evident in it, a gateway node is thus regarded as the urban design element that can be planned to create or enhance the image and identity of a its city. For the study, the chosen site is Cainta, a 4,000 Ha. town of Rizal strategically situated at the eastern periphery of Metro Manila, the business, financial and administrative capital of the Philippines. This town is envisioned by the local government as a Gateway of the East. People from Metro Manila pass by Cainta through the Radial Roads Marcos Highway and Ortigas Extension in order to go to Rizal, an urbanizing province located at the east of Metro Manila. And conversely, there is significant movement of people from Rizal and its eastern city and municipalities back to Metro Manila. Currently, the condition of the town's gateway points and activity nodes, face constraints that hinder the attainment of this vision. With these assertions, it is deemed necessary and beneficial to examine these areas, and find design solutions catered to enhance their identities. Three study areas in Cainta, namely V.V. Soliven Center, Cainta Junction and Cainta Downtown, were surveyed that were evaluated to have the potential to be developed into imageable gateway nodes. As an example of private-led design, a mixed-use transit oriented development in V.V. Soliven was conceptualized.